2015
DOI: 10.1515/hukin-2015-0122
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic Specificity of Plyometric Training: Verbal Cues Revisited

Abstract: Plyometric training is a popular method utilized by strength and conditioning professionals to improve aspects of functional strength. The purpose of this study was to explore the influence of extrinsic verbal cueing on the specificity of jumping movements. Thirteen participants (age: 23.4 ± 1.9 yr, body height: 170.3 ± 15.1 cm, body mass: 70.3 ± 23.8 kg,) performed four types of jumps: a depth jump “as quickly as possible” (DJT), a depth jump “as high as possible” (DJH), a countermovement jump (CMJ), and a sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Given the results for the CMJ and DJ, the use of force and velocity cues seems to have greater effects on movements involving the SSC. Previous literature agrees that adopting an external focus results in greater CMJ and DJ performance compared with using an internal or neutral focus (11,17,42,43), with DJ performance also being influenced by the specificity of a cue (24,31,32,44). The results from the current investigation indicate that a velocity cue provided some desirable changes during a CMJ and DJ, which could reflect enhanced SSC function (33).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Given the results for the CMJ and DJ, the use of force and velocity cues seems to have greater effects on movements involving the SSC. Previous literature agrees that adopting an external focus results in greater CMJ and DJ performance compared with using an internal or neutral focus (11,17,42,43), with DJ performance also being influenced by the specificity of a cue (24,31,32,44). The results from the current investigation indicate that a velocity cue provided some desirable changes during a CMJ and DJ, which could reflect enhanced SSC function (33).…”
Section: Discussionsupporting
confidence: 78%
“…However, this study has provided novel insight regarding how performance and kinetic outcomes change in adolescent athletes performing several different tasks with different external cues. This adds to previous similar research in child (i.e., 12 years or younger) athletes (32) and nonathletes (6,35) and adult moderately trained (11,13,17,31,44) and physically active populations (24,42,43).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Based on the differences recorded for the variables that describe CDJs and BDJs, it can be concluded that the study participants performed both types of jumps effectively. Therefore, it may be stated that the technique of the DJ is affected by the instruction to perform the exercise (Young et al, 1995; Jidovtseff et al, 2014; Khuu et al, 2015; Louder et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Drop jumps are a highly complex task for young athletes to develop proficiency in (6), however importantly, they are primarily used as a training tool to target fast or slow SSC function through progressive overload. Cueing shorter contact times during drop jumps typically encourages faster SSC activity, while cueing athletes to prioritise maximimum jump height may result in slower SSC actions (65). An increase in leg stiffness may result in reduced ground contact times, leading to a more efficient utilization of the SSC (1,55).…”
Section: Strength and Power Trainingmentioning
confidence: 99%